Analisis Yuridis Penegakan Hukum Korporasi di Bidang Lingkungan Hidup: Studi Kasus Putusan Pengadilan Negeri Batam Nomor 932/Pid.Sus/2020/PN Btm - Dekky Tiara Pra Setia; Markoni Markoni; Wasis Susetio; I Made Kanthika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Environmental damage in Indonesia is getting worse day by day. This condition has directly threatened human life. Environmental law enforcement is an action and/or process of coercion to comply with the law which is based on the provisions of statutory regulations. The aim of this research is to analyze efforts to resolve cases against corporations that damage the environment in Indonesia. Case Study Batam District Court Decision Number 932/Pid.Sus/2020/PN Btm. The method used in this research is normative juridical, namely library legal research carried out by examining library materials or secondary data. The results of his research are that law enforcement against corporations that damage the environment can be subject to criminal sanctions, administrative sanctions, and civil lawsuits can also be filed by the government. This is regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. The criminal sanctions received by PT. Kayla Alam Sentosa, who has intentionally committed an act that results in exceeding the Standard Criteria for Environmental Damage, is subject to a fine of Rp. 6,000,000,000,- (six billion rupiah). The conclusion is that criminal liability for corporations as perpetrators of environmental crimes is also subject to criminal penalties, apart from criminal penalties, they can also be subject to administrative sanctions, namely in the form of revocation of business permits. If it is deemed that the impact of environmental damage is greater than the criminal fine imposed, the corporation can also be sued civilly.